The Bath Advanced Neurology Course 2003: Progressive Neurological Decline in Pregnancy. Issue 3 (1st June 2005) - Joseph, Fady; Dawson, Ken; Betmouni, Samar; Moss, Tim; Smith, Philip
Abstract : THE CASE The story A young right-handed woman 30 weeks into her third pregnancy presented to the accident and emergency department with a 14-day history of headache; 7 days of progressive left-sided visual blurring, speech difficulties and vomiting; and 2 days of memory impairment, agitation and confusion. The early pregnancy had been uneventful, but at 22 weeks gestation she had been admitted with low back pain and urinary incontinence; MRI of the brain and spine were normal. There was a previous history of asthma, appendicectomy, and a miscarriage 3 years before, with a strong maternal family history of recurrent deep venous thromboses. Her only child had recently contracted chickenpox. Examination On initial examination she was poorly co-operative, confused, distressed and agitated. Registration and recall were reduced and she had nominal dysphasia. She was afebrile without meningism. Visual acuity was 6/6 on the right, but reduced to finger counting on the